2017
DOI: 10.1088/1612-202x/aa58bf
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of gradient polymer composites with nano-inclusions fabricated by laser assisted sintering

Abstract: Selective laser sintering (SLS) was used to prepare porous gradient polymer nanocomposites consisting of a polyetheretherketone (PEEK) matrix doped with alternating layers of Ni and Cu nanoparticles. Optimal regimes of such 3D-fabrication were determined. The functional graded (FG) structure of sintered parts was observed by optical and scanning electron microscopy and EDX microanalysis. Temperature dependence of electro-physical properties was studied for alternating ferromagnetic/non-magnetic layers (up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Laser ablation powered by inexpensive, robust, high-power nanosecond (ns) lasers appears to be a chemically clean, environmentally “green” key enabling process for industrial manufacturing of functional nanomaterials, for example nanoparticles (NPs), in liquids for diverse promising applications: Hydrogen generation, storage, and catalysis [ 1 , 2 , 3 ]; Wound healing, anti-cancer, anti-bacterial, and anti-fouling activity, and biosensing [ 4 , 5 , 6 , 7 , 8 , 9 ] in biomedicine; Additive nano-assembling of novel materials [ 10 , 11 , 12 , 13 , 14 ]; Non-linear nanophotonics [ 15 , 16 , 17 ]; NP-mediated/enhanced nuclear reactions [ 18 ] and many others (for the broad reviews, see, e.g., [ 19 , 20 , 21 , 22 , 23 ]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser ablation powered by inexpensive, robust, high-power nanosecond (ns) lasers appears to be a chemically clean, environmentally “green” key enabling process for industrial manufacturing of functional nanomaterials, for example nanoparticles (NPs), in liquids for diverse promising applications: Hydrogen generation, storage, and catalysis [ 1 , 2 , 3 ]; Wound healing, anti-cancer, anti-bacterial, and anti-fouling activity, and biosensing [ 4 , 5 , 6 , 7 , 8 , 9 ] in biomedicine; Additive nano-assembling of novel materials [ 10 , 11 , 12 , 13 , 14 ]; Non-linear nanophotonics [ 15 , 16 , 17 ]; NP-mediated/enhanced nuclear reactions [ 18 ] and many others (for the broad reviews, see, e.g., [ 19 , 20 , 21 , 22 , 23 ]). …”
Section: Introductionmentioning
confidence: 99%
“…in terms of laser power, repetition rates, and scanning velocities [ 21 , 30 , 31 ]. The more straightforward and practice-oriented stage three was well explored over the last decades [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], based on rather simple optical, electron microscopy, and dynamic light scattering characterization of the resulting colloids across the broad window of the laser and material parameters. Transient NP formation inside the laser-driven vapor bubbles (the intermediate stage two) was envisioned just recently via spatially- and temporally-resolved sophisticated X-ray transmission studies in liquids [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…He et al [25] fabricated Bi 0.5 Sb 1.5 Te 3 alloys via sterolithography additive manufacturing combined with thermal annealing at 350 • C under Ar gas to remove photoresins. Most recently, Shishkovsky et al [26] prepared porous gradient polymer nanocomposite materials consisting of a polyetheretherketone matrix doped with alternating layers of Ni and Cu nanoparticles via selective laser sintering additive manufacturing. To some extent, additive manufacturing may be an alternative to hot-pressing and spark plasma sintering methods for the preparation of inorganic TE materials [25].…”
Section: Introductionmentioning
confidence: 99%
“…Selective laser sintering (SLS) was used to prepare porous gradient polymer nanocomposites consisting of a polyetheretherketone (PEEK) matrix doped with alternating layers of Ni and Cu nanoparticles. It was reported that an insufficient agitation of mix led to a conglomeration of initial nanoparticles [86]. It was shown, that with the increase of layers number a figure of merit for multilayer system grows.…”
mentioning
confidence: 99%
“…It was shown, that with the increase of layers number a figure of merit for multilayer system grows. The FG 3D parts with alternating ferromagnetic Ni-PEEK and non-magnetic Cu-PEEK layers exhibited hysteresis phenomena, which may be useful for use in micro/nano-electro-mechanical systems (MEMS-NEMS) applications [86].…”
mentioning
confidence: 99%